PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT PERMATA PAMULANG DI TANGERANG SELATAN - Ridwan Rivai; Irwansyah Irwansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to determine the influence of Work Discipline and Work Motivation on Employee Performance at Permata Pamulang Hospital in South Tangerang either partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and the sample obtained in this study was 79 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, multiple regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Work Discipline and Work Motivation simultaneously have a positive and significant effect on Employee Performance. This can be proven by obtaining the regression equation Y= 2,007 + 0,372X1 + 0,473X2. The simultaneous correlation coefficient value is 0,773, meaning it has a “strong” relationship. And the coefficient of simultaneous determination is 0,598 or 59,8% while the remaining 40,2% is influenced by other factors. The hypothesis test was simultaneously obtained by Fcalculate > Ftable or (56,475 > 3,12) it was also strengthened by ρ value < Sig. 0.05 or (0.000 < 0.05). This means that there is a significant simultaneous influence of Work Discipline and Work Motivation on Employee Performance.